Alternatif Aljabar Untuk Bilangan Fuzzy Pentagonal - Tilopa, Era Napra; Mashadi, Mashadi (Universitas Islam Jember, 2025)
A part of the triangular fuzzy numbers, is what we call pentagonal fuzzy numbers. Plentyof alternatives for fuzzy pentagonal numbers are suggested by some writers. Particularlyfor scalar summation, subtraction, and multiplication, there is no enormous diversity.However, for multiplication, division, and inverse as well, there are so many algebraicoptions proposed by various scholars. Some writers defined the form of inverse for pentagonal fuzzy numbers in parametric. But it does not always result in identity. Sucha thing will also have implications in the process of how to invers the pentagonal fuzzynumbers matric. This paper proposes an alternative method to decide the inverse ofpentagonal fuzzy numbers, in the form of parametric. The first thing to do is toconstruct two midpoint for any pentagonal fuzzy. The midpoint are used to constructthe multiplication, division and inverse. Algebraic to any pentagonal fuzzy number inany single inverse such that it produces an identity inverse, likewise for a pentagonal fuzzy number matrix it produces an identity matrix inverse. Keywords: Algebraic Alternative Fuzzy Number; Inverse Of Penthagonal Fuzzy Number Matric